Computational modeling of carbon nanofibers reinforced composites: A comparative study. (July 2021) - Bian, Pei-Liang; Qing, Hai
The carbon nanotubes/nanofibers reinforced composites (CNRC) show great mechanical properties. There are several methods to simulate the mechanical properties of composites. Among the modeling techniques, embedded region (ER) shows the possibility for direct multi-scale simulation. A comparative study among beam element embedded model, solid element embedded model, as well as common solid element model is carried out. Programs developed in Matlab are utilized to generate geometric configurations, and finite element models are obtained from MSC.Patran with a script written in the Patran command language (PCL). Besides, a set of parametric studies are performed to investigate the influence of the aspect ratios of nanofibers and load cases on the mechanical properties of CNRC. The result shows that the ER technique is reliable to represent composites though neglecting the localized stress concentration, and beam element embedded models are trustworthy only for nanofibers with a large aspect ratio.